The treasures of Alexander the Great : how one man's wealth shaped the world - Holt, Frank Lee, (Onassis series in Hellenic Culture., 2016)
"War, the most profitable economic activity in the ancient world, transferred wealth from the vanquished to the victor. Invasions, sieges, massacres, annexations, and mass deportations all redistributed property with dramatic consequences for kings and commoners alike. No conqueror ever captured more people or property in so short a lifetime than Alexander the Great in the late fourth century BC. For all its savagery, the creation of Alexander's empire has generally been hailed as a positive economic event for all concerned. Even those harshly critical of Alexander today tend to praise his plundering of Persia as a means of liberating the moribund resources of the East. To test this popular interpretation, The Treasures of Alexander the Great investigates the kinds and quantities of treasure seized by the Macedonian king, from gold and silver to land and slaves. It reveals what became of the king's wealth and what Alexander's redistribution of these vast resources can tell us about his much-disputed policies and personality. Though Alexander owed his vast fortune to war, battle also distracted him from competently managing his spoils and much was wasted, embezzled, deliberately destroyed, or idled unprofitably. The Treasures of Alexander the Great provides a long-overdue and accessible account of Alexander's wealth and its enormous impact on the ancient world"--